2014
DOI: 10.4236/ami.2014.44006
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Mediterranean Diet and Biomarkers-Assessed Risk of Alzheimer’s: A Multi-Modality Brain Imaging Study

Abstract: Increased physical activity and higher adherence to a Mediterranean-type diet (MeDi) have been independently associated with reduced risk of Alzheimer’s disease (AD). Their association has not been investigated with the use of biomarkers. This study examines whether, among cognitively normal (NL) individuals, those who are less physically active and show lower MeDi adherence have brain biomarker abnormalities consistent with AD.MethodsForty-five NL individuals (age 54 ± 11, 71% women) with complete leisure tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 49 publications
9
54
0
1
Order By: Relevance
“…The effects of lifestyle on amyloid deposition in our study are similar to those found in studies with participants with high education (median ≥16 years). 6 10 There is also literature supporting our findings of reduced AD risk due to lifestyle modification, specifically in APOE4 carriers. 10 , 27 30 The analyses conducted in this article make an important point that high-education cohorts are likely to find an association of high lifestyle enrichment with low amyloid deposition.…”
Section: Discussionsupporting
confidence: 81%
“…The effects of lifestyle on amyloid deposition in our study are similar to those found in studies with participants with high education (median ≥16 years). 6 10 There is also literature supporting our findings of reduced AD risk due to lifestyle modification, specifically in APOE4 carriers. 10 , 27 30 The analyses conducted in this article make an important point that high-education cohorts are likely to find an association of high lifestyle enrichment with low amyloid deposition.…”
Section: Discussionsupporting
confidence: 81%
“…Diet quality has been shown to be related to the volume of the hippocampus (the brain structure that is mainly associated with learning and memory) [ 81 ]. In elderly humans, MeDi has been associated with reduced brain atrophy [ 82 ] and reduced amyloid peptides load in the brain [ 83 ]. In our study, the relative risk for all dementias was identical with the relative risk for Alzheimer’s disease related dementia, while memory was the only cognitive domain consistently associated with MedDietScore, in fully adjusted models and in all cognitive status groups.…”
Section: Discussionmentioning
confidence: 99%
“…Apropos to the current study, Matthews and colleagues [11] investigated the relationship between leisure time PA and cerebral glucose metabolism. Utilizing the Minnesota Leisure Time Activity questionnaire, they found that individuals who engaged in the equivalent of at least 30 minutes of moderate activity five days a week had significantly higher levels of glucose metabolism in regions including the parahippocampal gyrus, fusiform gyrus, and middle temporal gyrus, compared to their physically inactive peers.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) has been shown to be associated with many indices of brain health [810] including cerebral glucose metabolism [11]. However, these studies have measured PA with questionnaires, which are subject to recall and social desirability biases [12].…”
Section: Introductionmentioning
confidence: 99%